Interdependence Between the CAC40 and the DAX Indices in Intraday Data - Będowska-Sójka, Barbara (Zależności pomiędzy indeksami CAC40 i DAX w danych śróddziennych, 2011)
This paper seeks to find out if shocks observed on the French and German markets are observed at the same moment or are transmitted among the markets within the very short time period. The bivariate GARCH model is estimated with variables standing for shocks in order to examine if there exists interdependence between the markets. The sample consists of 5-minute returns of the CAC40 and the DAX. Using high-frequency data and within the framework of the dynamic conditional correlation models, we show that volatility increases at the same time in the series. Within the nearest 5-minute interval, shocks observed in the DAX returns increase volatility of CAC40. Our results indicate co-movement in this pair of indices which suggests common exogenous sources of volatility shocks
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2011; Nr 194, s. 143-152
Keywords: rynki finansowe; zmienność; indeks giełdowy; financial markets; variability; stock market indexes